2013
DOI: 10.1590/s0102-67202013000200017
|View full text |Cite
|
Sign up to set email alerts
|

Curativo à vácuo para cobertura temporária de peritoneostomia

Abstract: The vacuum dressing proved to be good choice for temporary coverage of peritoneostomies allowing faster closure of the abdominal wound, reducing the number of reoperations and providing protection against bacterial contamination of the intestinal loops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Therapy with vacuum dressing showed several advantages in managing trauma patients or those with severe intra abdominal infections, thus reducing postoperative morbimortality rates. It effectively prevents fluid loss and bacterial contamination [10] , [11] . In our patient, the use of vacuum therapy was crucial during the entire hospital stay, in reducing both surgical and recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with vacuum dressing showed several advantages in managing trauma patients or those with severe intra abdominal infections, thus reducing postoperative morbimortality rates. It effectively prevents fluid loss and bacterial contamination [10] , [11] . In our patient, the use of vacuum therapy was crucial during the entire hospital stay, in reducing both surgical and recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Birolini et al were successful in a retrospective trial of 20 patients with complications. They concluded that the application of synthetic materials did not have to be avoided in cases of abdominal infection, when classical principles of surgery, such as antisepsis and hemostasia, were respected 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo o curativo sob pressão negativa estimula a perfusão tecidual além de reduzir a tensão sobre as bordas, minimizando o risco de necrose, promovendo uma contração e aproximando as bordas (SIMÃO TS, et al, 2013). Barker DE, et al (2012) foram pioneiros em descrever essa técnica, alcançaram 55,4% dos casos de fechamento parietal, e com poucas complicações.…”
Section: Curativo a Vácuo Em Pacientes Com Peritoniostomiaunclassified